Standardising 400 years of speech: Norsk Ordbok and its dialect materials - Grønvik, O; Wetås, Å (2010)
Norwegian linguistic history has documentation gaps, resulting from Old Norse being replaced with Danish (ca 1400-1900), which again was replaced with two written would-be standards, Nynorsk (1860 onwards) and Bokmål (from ca 1900, originally Danish modified towards educated Noregian speech). In the 20th century, both standards were modified several times, and they are now fairly close to each other, but still distinct. Norsk Ordbok (NO 2014) is a twelve volume academic dictionary covering Nynorsk literature since the Nynorsk standard took form around 1860, and Nowegian dialects from 1600 onwards. The project started in 1930, was digitised from 1991 onwards, and is pledged to finish its twelth volume by the end of 2014. Since 2003 the editorial platform has been wholly digital. The lexicographic principle behind NO 2014 is that every dialect word can be expressed in the standard orthography and belongs in written Nynorsk. This premise is expressed in an index linking speech and the written standard (the Meta Dictionary). Oral materials have been collected and included both from the synchronic and the diachronic angle since project start in 1930. Older materials comprise dialect word lists from 1600 onwards and dialect texts. Plans are afoot to digitise the whole dialect corpus 1600-1850, emphasising philology combined with maximum accessibility. Collections of synchronic oral materials started in 1930. They comprise transcribed speech, recordings and maps of Norwegian linguistic phenomena. NO 2014 also uses digitised text collections, parts of which are dialect based and difficult to search. Challenges in dealing with the dialect materials include identifying dialect forms with standard forms, sorting out etymologies and establishing word maps for all meanings. Project speed requires transparent organisation of materials. Public funding requires easy access to all. In this paper, we would like to show how these issues are handled.